Field strength dependence reveals multiple sources of relaxation anisotropy in single and crossing white matter fibers - Melanie Bauer; Christian Kremser; Elke R. Gizewski; Claudia Lenz; Christoph Birkl (NeuroImage, 2025)
Quantitative magnetic resonance imaging (MRI) parameters depend on the orientation of white matter fibers relative to the main magnetic field. However, the impacts of fiber complexity and field strength remain unclear.This study investigated the effects of fiber complexity and field strength on the orientation dependency of the irreversible transverse relaxation rate R2, the effective transverse relaxation rate R2* and the reversible transverse relaxation rate R2’ (= R2* - R2) in the human brain. Nine healthy volunteers underwent MRI at 1.5 T and 3 T, allowing the assessment of orientation dependence in single and crossing fibers as well as the evaluation of field strength-dependent and -independent components.All relaxation rates, except R2 at 1.5 T, differed significantly between single and crossing fibers. R2*, R2’, and their anisotropies were significantly higher at 3 T compared to 1.5 T. Both field strength-dependent and -independent components showed orientation dependence, exhibiting higher values for fibers perpendicular to the field. Notably, the field strength-independent component of R2* displayed a unique pattern, reaching a maximum at 45° and a minimum at 85°.These findings suggest that both field strength-dependent and -independent components contribute to relaxation anisotropy in white matter, thereby indicating multiple sources of anisotropy. This study provides valuable insights into the complex relationship between white matter fiber orientation, field strength and quantitative MRI parameters, paving the way towards advanced understanding of white matter imaging.